2000
DOI: 10.1063/1.125622
|View full text |Cite
|
Sign up to set email alerts
|

Electrical characterization of isoelectronic In-doping effects in GaN films grown by metalorganic vapor phase epitaxy

Abstract: Indium isoelectronic doping was found to have profound effects on electrical properties of GaN films grown by metalorganic chemical vapor deposition. When a small amount of In atoms was introduced into the epilayer, the ideality factor of n-GaN Schottky diode was improved from 1.20 to 1.06, and its calculated saturation current could be reduced by 2 orders of magnitude as compared to that of the undoped sample. Moreover, it is interesting to note that In isodoping can effectively suppress the formation of deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(22 citation statements)
references
References 14 publications
2
20
0
Order By: Relevance
“…Only one of these traps, the T2 trap, has been reported in the literature. This trap, with the activation energy at E C − 0.50 ÷ 0.62 eV and labelled B2, D2, or E2 in the literature, tends to be the most prominent electron trap revealed by DLTS in n-type GaN [10][11][12][13][14][15]. Hacke et al [12] and Haase et al [13] assigned this trap to the nitrogen antisite point defect, N Ga , on the ground of the results of tight-binding calculations determining the deep donor level of N Ga at E C − 0.54 eV [16].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Only one of these traps, the T2 trap, has been reported in the literature. This trap, with the activation energy at E C − 0.50 ÷ 0.62 eV and labelled B2, D2, or E2 in the literature, tends to be the most prominent electron trap revealed by DLTS in n-type GaN [10][11][12][13][14][15]. Hacke et al [12] and Haase et al [13] assigned this trap to the nitrogen antisite point defect, N Ga , on the ground of the results of tight-binding calculations determining the deep donor level of N Ga at E C − 0.54 eV [16].…”
Section: Discussionmentioning
confidence: 79%
“…Hacke et al [12] and Haase et al [13] assigned this trap to the nitrogen antisite point defect, N Ga , on the ground of the results of tight-binding calculations determining the deep donor level of N Ga at E C − 0.54 eV [16]. More recent results by Chung et al [14] and Cho et al [10], showing that the concentration of this trap could be effectively suppressed by In doping, support this assignment. Very recently, this trap has been also revealed as the dominant deep-level defect in MOVPE-grown LD heterostructure [11].…”
Section: Discussionmentioning
confidence: 94%
“…Hacke et al [18] and Haase et al [19] assigned this trap to the nitrogen antisite point defect, N Ga , on the grounds of the results of tight-binding calculations determining the deep donor level of N Ga at E C − 0.54 eV [25]. More recent results by Chung et al [20] and Cho et al [15], showing that the E2 trap concentration could be effectively suppressed by In doping, support this assignment since isoelectronic In atoms, occupying vacant Ga sites in the GaN crystal lattice during the growth, result in a lowering the density of Ga vacancy-related defects. However, several authors revealed that the E2 traps displayed the logarithmic capture kinetics [14,16] and that their concentration increased with the increase of dislocation density [16,22,24], and concluded that the traps were associated with dislocations themselves or were created during the dislocation generation process.…”
Section: Dlts Resultsmentioning
confidence: 95%
“…This level has been reported by several authors, and in many reports it has been associated with the nitrogen antisite (N Ga ). 5,6,9,27 More recently, Look et al 10 performed measurements before and after 1 MeV electron irradiation of HVPE grown GaN sample, and they did not observe any changes in concentration for this trap. Considering this and that it is an electron trap relatively close to the conduction band, they suggested that this level is associated with some more complex defect involving a common impurity such as Si, O, or C or possibly C Ga .…”
mentioning
confidence: 99%